SANKSI ADAT TERHADAP PARA PELAKU PENCABUTAN PENJOR DI WILAYAH TARO TEGALLALANG KABUPATEN GIANYAR - Darma, Gede; Herawati, Kadek Mery; Laksmiwati, Lya Meinar (Kerta Dyatmika, 2024)
This study is motivated by a customary law violation involving the removal of a penjor in Taro Traditional Village, Tegallalang, which triggered tensions between customary law and national law. The objective of this research is to examine the application of customary sanctions against perpetrators of such violations and to analyze the preventive measures taken by Taro Traditional Village to avoid the recurrence of similar incidents. The research employs a normative juridical approach combined with empirical legal research, focusing on the implementation of positive legal norms within the community. Data were collected through literature review and field interviews. The findings reveal that the seven traditional officials (prajuru) of Taro Kelod who were implicated in the penjor removal were not subjected to customary sanctions, as the victim was under an existing customary sanction of kasepekang (social exclusion). However, they were convicted under national law and sentenced to eight months of imprisonment for committing a criminal offense of religious blasphemy, in accordance with Article 156a in conjunction with Article 55 paragraph (1) point 1 of the Indonesian Criminal Code (KUHP). Preventive efforts include maximizing the role of traditional authorities such as the bendesa adat, prajuru desa, and wali desa to enhance supervision and coordination. The traditional village has also sought to strengthen its awig-awig (customary law) by incorporating specific pararem (customary bylaws) regulating violations such as the removal of penjor or other religious ceremonial objects, while fostering a correlation between customary and national legal systems and raising legal awareness among the community. Repressive measures involve sharpening sanctions through a review of the awig-awig in customary council meetings (paruman adat) and urging greater caution among traditional authorities before taking actions that may constitute violations. In cases of similar violations, customary adjudication may be pursued through paruman adat. The study concludes that although customary law remains the primary reference within the traditional community, a harmonious integration between customary and national law is essential to uphold order, justice, and the preservation of cultural values in society.